Creating an Open Online Educational Resource to Support Learners as They Navigate Their Studies Alongside Work and/or Family - Waterhouse, Philippa; Moller, Naomi (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2024)
As labour markets undergo rapid and profound transformations, lifelong learning is essential to ensure a responsive, competitive, and skilled workforce. Mature learners are a diverse group, but in comparison to their younger student counterparts, are more likely to have employment and/or caring responsibilities. This field note discusses the development and features of a novel online open educational resource, called At a crossroads: Navigating work and/or family alongside study (At a crossroads for brevity). The resource aimed to assist university students to both learn about the support options available to them as well as to consider how they themselves might make decisions if they experienced a conflict between their student/work/family roles. At a crossroads is innovative in terms of how it was developed (i.e., via survey-based research, story completion method, and consultations sessions with tertiary students) and in terms of what it is (i.e., an online interactive resource that incorporates short dramatizations, social polls, and opportunities to reflect). Our experience in developing this resource caused us to consider how making resources designed to be engaging and informative, while encouraging, positive changes, must be part of the solution. This is especially so when there is significant concern around the overall well-being of tertiary students and their course completion rates. While universities have attempted to offer a range of tools to support their students, on-demand online resources such as At a crossroads are easily accessed, free to use, and deliver content in an engaging manner.